Optimization of HIV-1 infectivity assays. (November 2007) - Jones, Jennifer; Whitford, William; Wagner, Frederic; Kutsch, Olaf
HIV-1 reporter cell lines are the backbone of diagnostic assays, vaccine and drug development efforts. Performing HIV-1 infection experiments in a T cell background is desirable for many reasons. However, a low susceptibility to infection with primary patient isolates in available reporter T cell lines has limited such efforts. We here demonstrate that optimization of HIV-1 receptor expression and the utilization of serum free medium compositions can increase susceptibility of reporter T cell lines to HIV-1 infection by up to two orders of magnitude.